PROKSIMAT DAN ASAM LEMAK JUVENIL IKAN MAS (Cyprinus carpio) PADA BERBAGAI UMUR PANEN - Jacoeb, Agoes M.; Nurjanah, Nurjanah; Sitanggang, Laurensius (Coastal and Marine Resources Research Center, Raja Ali Haji Maritime University, Tanjungpinang, Indonesia, 2015)
Carp as food is processed into various products, including pepes, bekasam, fried carp, as well as new products such as fried carp made from juvenile fish. The purpose of this study was to determine the proximate, the type and amount of fatty acids juvenile carp at harvest age 3, 5, and 7 weeks. Protein and ash content increased from harvest age 3 weeks to 5 and 7 weeks while the fat content decreased. Fatty acid profile consisting of 5 types of SAFA, 1 type of MUFA, and 3 type of PUFA 3. Oleic fatty acid is a predominant fatty acid. The content of SAFA decreased with increasing age of harvest, i.e from 36.36% (3 weeks) to 30.78% (5 weeks) and 10.04% (7 weeks). Instead PUFA content increased from 17.93% (3 weeks) to 20.09% (5 weeks) and 44.25% (7 weeks).